Karakteristik Pendertia Snakebite Disertai Gangguan Hemodinamik dan Asidosis Respiratorik pada Pasien Anak dan Dewasa - Afif Ferdian; R. Mohamad Javier; Himawan Wicaksono; Budi Prakoso; Djanuar Fitriadi; Zainuddin Hamidi (Jurnal Health Sains, 2023)
Snakebite or snakebite is a defense mechanism for snakes and can become a medical emergency. Snakebites are a significant cause of morbidity and mortality worldwide, especially in South and Southeast Asia, sub-Saharan Africa and Latin America. The snakebite can be life-threatening if it has a neurotoxic, cytotoxic and hemotoxic effect. Complications from snakebite include hemodynamic disturbances and respiratory acidosis. International online databases (PubMed and Google Scholar) were used to search for articles in this systematic review. A total of 24 related research articles indexed by Scopus have been published in the last ten years. This research is a literature systematic review. Research sources were taken in the last 10 years from 2012 to 2022, taken from PubMed and Google Scholar. After exclusion, 24 articles and studies that met the exclusion and inclusion criteria were considered for systematic review. Of all the journals reviewed, there are many that explain snake bite associated with hemodynamic disturbances and respiratory acidosis. Snakebite is proven to provide long-term complications in the form of hemodynamic disturbances around the bite site. Another complication that has been proven to occur in snakeibite victims is cardiac shock, especially impaired cardiac return. Pathophysiology, symptoms, and diagnosis of snakebite in pediatric and adult patients are the same. The majority of journals discuss heart disorders and infections, necrosis of muscles and bones related to venomous snake bites. Hemodynamic disturbances and respiratory acidosis are complications that can occur in snakebite victims. There are similarities in symptoms and management of venomous snake bites in children and adults.